Penerapan Data Mining Dalam Klasifikasi Pola Minat Mahasiswa Stikom Tunas Bangsa Melakukan Vaksinasi Menggunakan Algoritma Naive Bayes - Muhammad Irfani; Dedy Hartama; Muhammad Ridwan Lubis; Renaldi; Wendi Robiansyah (SNASTIKOM, 2023)
Vaccination is a process in the body, where a person becomes immune or protected from a disease so that if one day they are exposed to the disease they will not get sick or only experience mild illness, usually by administering a vaccine. This research has the problem of not using the Naïve Bayes algorithm to classify students' interest patterns in carrying out vaccinations at STIKOM Tunas Bangsa Pematangsiantar. The data used in this research is questionnaire data. Application of the Naive Bayes method with questionnaire data taken from STIKOM Tunas Bangsa Pematangsiantar students in order to find out possible interest patterns of students who take vaccines